Pembuatan Peta Foto Udara Menggunakan Drone DJI Phantom 4 RTK dalam Pembelajaran Berbasis Proyek di Tanjung Riau, Kota Batam - Roziqin, Arif; Gustin, Oktavianto; Irawan, Sudra; Lubis, Muhammad Zainuddin; Pratama, Rizki Widi; Rassarandi, Farouki Dinda; Sari, Luthfiya Ratna; Chayati, Siti Noor; Raptama, Mulia; Silvia, Ega; Haadi, Maulana Rafly Al; Zahra, Mulyani Aprilia; Sormin, Naomi Septania; Nova, Dithia Mardi; Adha, Muhammad; Sebayang, Amira Leoni Br; Lubis, Alwi Raihan; Nazara, Kasih Riang Bohouni (Politeknik Negeri Batam, 2023)
The rapid development of large-scale infrastructure in Indonesia indicates the need for solutions for fast crack applications with accurate results using methods that are efficient in terms of time and data generated. One example of the development of mapping technology in this modern era is aerial photography not only using manned aircraft, but you can also use an unmanned aerial vehicle or UAV (Unmanned Aerial Vehicle). This unmanned aircraft is better known as a drone, which is currently at an affordable price, easy to get and has the ability to shoot like a manned aircraft. Measurements were made using photogrammetric techniques from aerial photographs produced by drones. With results that have high accuracy, and can be done in the shortest possible time, then the use of drones in making topographic maps will be more widely used in the future. In our study and research survey that we conducted in the form of PBL (Project Based Learning) Politeknik Negeri Batam students in community service in the soaking village, Tanjung Riau, Batam Island, namely for making aerial photo maps using the DJI Phantom 4 RTK drone which we carried out in the village soak.